Fish consumption pattern in Purba Medinipur district of West Bengal - Salim, Shyam S; Stanley, Lowrane; M, Shinu A.; Sen, Swatipriyanka (Journal of the Inland Fisheries Society of India, 2022)
Fish consumption is determined by the level of income and its easy availability, affordability and accessibility. The consumption of fish is increasing significantly due to varying taste and preferences, lifestyle changes and higher cost of protein substitutes like meat and meat products. The determinants of fish demand and the consumption pattern differ across regions, seasons, income levels, beliefs, customs and traditions, besides several other factors.The present study was carried out in Purba Medinipur district of West Bengal to find out the fish consumption profile of selected households and to identify the factors that drive people for fish consumption. A total of 253 respondents have been selected using purposive sampling method and interviewed for obtaining pertinent data. The study revealed that the average monthly household fish consumption across the study area was 7.65 kg. Majority of the non-vegetarian consumers in the study area had the highest preference for fish followed by chicken, and mutton. The average monthly expenditure on fish per family in the study area constituted 26.64% of overall total food expenditure. Majority of consumers (69.6%) consumed fish on daily basis, 22.1% alternatively, 4% of the respondents twice in a week and only 4.3 % consumed fish once a week. Among different factors, freshness and taste of fish influenced fish consumption.There were some limiting factors in augmenting fish consumption high price of fish followed by irregular supply and wide fluctuations in price. Different statistical and econometric tools such as RESEARCH PAPER conjoint analysis, preference assessment index were deployed for analyzing the data.The study suggests that to make regular supply and availability of fish at lower price the state government should focus on productivity enhancement programs in small water bodies, aquaculture development, and better utilization of small pelagic fish for increasing food fish supplies in the region.Key words Fish consumption; Conjoint analysis; Preference assessment index; Garrette ranking